How many begomovirus copies are acquired and inoculated by its vector, whitefly (Bemisia tabaci) during feeding? - Buddhadeb Roy (Public Library of Science (PLoS), 2021)
Begomoviruses are transmitted by whitefly (Bemisia tabaci Gennadius, Hemiptera: Aleyrodidae) in a persistent-circulative way. Once B. tabaci becomes viruliferous, it remains so throughout its life span. Not much is known about the copies of begomoviruses ingested and/or released by B. tabaci during the process of feeding. The present study reports the absolute quantification of two different begomoviruses viz. tomato leaf curl New Delhi virus (ToLCNDV, bipartite) and chilli leaf curl virus (ChiLCV, monopartite) at different exposure of active acquisition and inoculation feeding using a detached leaf assay. A million copies of both the begomoviruses were acquired by a single B. tabaci with only 5 min of active feeding and virus copy number increased in a logarithmic model with feeding exposure. Whereas, a single B. tabaci could inoculate 8.21E+09 and 4.19E+11 copies of ToLCNDV and ChiLCV, respectively in detached leaves by 5 min of active feeding. Virus copies in inoculated leaves increased with an increase in feeding duration. Comparative dynamics of these two begomoviruses indicated that B. tabaci adult acquired around 14-fold higher copies of ChiLCV than ToLCNDV 24 hrs post feeding. Whereas, the rate of inoculation of ToLCNDV by individual B. tabaci was significantly higher than ChiLCV. The study provides a better understanding of begomovirus acquisition and inoculation dynamics by individual B. tabaci and would facilitate research on virus-vector epidemiology and screening host resistance.